Committed and Engaged: The Contribution of Positive Experienced Teachers - Gibson, Eric B. (International Journal on Studies in Education, 2025)
This hermeneutical phenomenological study examines the contributions in the lived experiences of positive experienced teachers with more than five years of teaching experience. This study’s research question was: What contributions increase the autonomy, competence, and connection in the school communities in the lived experiences of positive experienced teachers who remain committed and engaged? Data were collected from 15 teachers from four continents who have remained committed and effective in their teaching practice. Key themes emerged, including promoting communication, developing community, fostering a growth mindset, and providing support. The study concluded that positive experienced teachers: know and connect to their students, prioritize creating a learning environment, bring willing teachers alongside, and benefit their whole school community. Notably, these educators placed a unique emphasis on building positive classroom community and communication while supporting growth-oriented teachers practically and emotionally and seeking increased connectivity and growth for their whole school communities.